Endothelial MicroRNA-483-3p Is Hypertension-Protective. (17th February 2022) - Shang, Fenqing; Guo, Xuan; Chen, Yueer; Wang, Chen; Gao, Jie; Wen, Ergang; Lai, Baochang; Bai, Liang
Abstract : Hypertension is a high-risk factor for developing coronary heart disease and stroke. Endothelial dysfunction and arterial remodeling can lead to increased vascular wall thickness and arterial stiffness. Previous studies showed that microRNA-483 (miR-483) enhances endothelial cell (EC) function. Here, we investigated the protective role of miR-483 in hypertension. Data collected from two patient cohorts showed that the serum miR-483-3p level was associated with the progression of hypertension and positively correlated with vascular function. In cultured ECs, miR-483 targets a number of endothelial dysfunction-related genes, such as transforming growth factor- β (TGF- β ), connective tissue growth factor (CTGF), angiotensin-converting enzyme 1 (ACE1), and endothelin-1 (ET-1). Overexpression of miR-483-3p in ECs inhibited Ang II-induced endothelial dysfunction, revealed by the decreased expression of TGF- β, CTGF, ACE1, and ET-1. Furthermore, miR-483-3p secreted from ECs was taken up by smooth muscle cells (SMCs) via the exosome pathway, which also decreased these genes in SMCs. Additionally, telmisartan could increase the aortic and serum levels of miR-483-3p in hypertension patients and spontaneous hypertension rats (SHR). These findings suggest that miR-483-3p exerts a protective effect on EC function during the onset of hypertension and thus may be considered a potential therapeutic target for hypertension-related cardiovascular diseases.